Efficacy and safety of empagliflozin as add‐on to insulin in Japanese patients with type 2 diabetes: A randomized, double‐blind, placebo‐controlled trial. Issue 3 (20th December 2019) - Sone, Hirohito; Kaneko, Tatsuroh; Shiki, Kosuke; Tachibana, Yoshifumi; Pfarr, Egon; Lee, Jisoo; Tajima, Naoko
Abstract : Aim: To assess the efficacy and safety of empagliflozin as add‐on to insulin in Japanese patients with type 2 diabetes (T2D). Materials and methods: This multicentre, double‐blind, parallel‐group study randomized Japanese patients with T2D insufficiently controlled with insulin (1:1:1) to empagliflozin 10 mg (n=89), empagliflozin 25 mg (n=90) or placebo (n=90) for 52 weeks. The primary endpoint was change from baseline in glycated haemoglobin (HbA1c) at 16 weeks. Results: At 16 weeks, empagliflozin 10 mg and 25 mg significantly decreased HbA1c: adjusted mean difference −0.92% (95% confidence interval [CI] −1.11, −0.73) and −1.00% (95% CI −1.18, −0.82; both P <0.0001) compared with placebo. This difference was maintained up to 52 weeks: adjusted mean difference at 52 weeks −0.90% (95% CI −1.09, −0.70) and −0.96% (95% CI −1.15, −0.77; both P <0.0001). At 52 weeks, significant improvements in fasting plasma glucose (adjusted mean difference −27.62 mg/dL [95% CI −36.15, −19.08] and −31.99 mg/dL [95% CI −40.35, −23.62]) and in body weight (−1.78 kg [95% CI −2.46, −1.10] and −1.92 kg [95% CI −2.58, −1.25]) were also seen with empagliflozin 10 mg and 25 mg compared with placebo (all P <0.0001). At 52 weeks, the frequency of adverse events (AEs) and serious AEs was similar in the three treatment groups; confirmed hypoglycaemia was reported slightly more in participants in the empagliflozin 10 mg and 25 mg groups (23.3% and 22.2% vs 14.4%). All hypoglycaemic events were mild in severity; no episodes required assistance. Conclusions: In Japanese patients with insufficiently controlled T2D, adding empagliflozin 10 mg or 25 mg to insulin treatment was associated with clinically meaningful reductions in HbA1c at 16 weeks and was generally well tolerated.